Loss in Translation of Culture-Specific Items in Laskar Pelangi from Indonesian to Japanese - Riska Aristya; Sajarwa Sajarwa (Journal of Social Research, 2026)
This study addresses the challenges of translating culture-specific items in literary texts, particularly focusing on the phenomenon of meaning loss in the Indonesian novel Laskar Pelangi and its Japanese translation. The objective of this research is to identify the types of loss occurring in the translation process and to examine their implications for translation equivalence. The study employed a qualitative descriptive approach, using data derived from the source text and its Japanese version. Data were collected through documentation techniques and analyzed using translational equivalence, descriptive, comparative, and interpretive methods. The findings reveal that out of 572 identified culture-specific items, 294 (51.4%) experienced loss, categorized into untranslated words, inaccurate translation, generalization, adaptation, and paraphrasing. Inaccurate translation emerged as the most dominant type of loss. The study further shows that these losses lead to two forms of equivalence: partial equivalence and non-equivalence, with non-equivalence occurring more frequently. In conclusion, the translation tends to prioritize target-language readability through domestication strategies, which often results in cultural meaning loss. The study highlights the importance of cultural competence in translation to minimize loss and improve equivalence, especially in culturally rich literary works.